2022
DOI: 10.3389/fpsyg.2021.768429
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Effective Transitions From University to Post-graduation for Autistic Students

Abstract: BackgroundThe number of autistic students graduating is increasing; however, little is known regarding their transition out of university. Understanding this transition is particularly pertinent with regard to the employment of autistic graduates. It is vital that we understand autistic people’s experiences of the transition and identify what support would be beneficial during this time.MethodThirty-four autistic graduates from the United Kingdom took part in a mixed-methods study exploring their transition ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…They believed that their time in university helped them acquire a variety of life skills, such as taking initiative and communication (Hadley, 2018;O'Byrne et al, 2019;Vincent, 2019). On the other hand, some reported lack of preparation for employment (Büscher-Touwen et al, 2018;Hewett et al, 2021;Lessy et al, 2021;Lucas et al, 2022). While organisation factors (career counselling and placements) were found to facilitate the transition to work, persons with autism found self-direction still difficult and therefore greatly appreciated the individualised support that was received through caring lecturers and mentors (Ule, 2017;Pesonen et al, 2021).…”
Section: Subtheme 14: Need To Be Prepared For Employmentmentioning
confidence: 99%
“…They believed that their time in university helped them acquire a variety of life skills, such as taking initiative and communication (Hadley, 2018;O'Byrne et al, 2019;Vincent, 2019). On the other hand, some reported lack of preparation for employment (Büscher-Touwen et al, 2018;Hewett et al, 2021;Lessy et al, 2021;Lucas et al, 2022). While organisation factors (career counselling and placements) were found to facilitate the transition to work, persons with autism found self-direction still difficult and therefore greatly appreciated the individualised support that was received through caring lecturers and mentors (Ule, 2017;Pesonen et al, 2021).…”
Section: Subtheme 14: Need To Be Prepared For Employmentmentioning
confidence: 99%
“…(Accardo et al, 2019a;Lei and Russell, 2021;Sefotho and Onyishi, 2021) • Lack of housing accommodations and independent living supports (Simmeborn Fleischer et al, 2013;Cullen, 2015; • Struggles with lack of routine and lack of structure (Lei and Russell, 2021) • Stressors from living situation (Cullen, 2015;Bolourian et al, 2018) Vocational • Employment and career support from peer mentors, tutors, coaches, faculty, DSO, and mental health staff (Gunn et al, 2017;Cheriyan et al, 2021;Pesonen H. V. et al, 2021;Ames et al, 2022) • Career services and career centers (Briel and Getzel, 2014;Barnhill, 2016;Cheriyan et al, 2021) • Career counseling and academic advising (Weiss and Rohland, 2015;Pesonen H. V. et al, 2021;Lucas et al, 2022) • Support with job-seeking skills (applying for jobs, resume writing, interview skills, etc.) (Retherford and Schreiber, 2015;Vincent and Fabri, 2020;Cheriyan et al, 2021;Munandar et al, 2021) • Internships or practicums (Pesonen H. V. et al, 2021) • Lists of autism-friendly employers or referral to autism related organization (Vincent et al, 2022) • Lack of employment supports, lack of awareness of existing supports, or existing supports were not helpful (Briel and Getzel, 2014;Pesonen H. V. et al, 2021) • Need for individualized, flexible, and targeted career assistance (Pesonen H. V. et al, 2021; • Lack of career guidance/training Lucas et al, 2022) • Transition to employment identified as a stressor (Van Hees et al, 2015;Bolourian et al, 2018;Ames et al, 2022) • Desire for support developing a disclosure plan for future employers…”
Section: Categories Contributors Challengesmentioning
confidence: 99%
“…• Lack of supports for the life changes of transitioning out of university (aside from employment supports) (Lei and Russell, 2021;Lucas et al, 2022;Vincent et al, 2022) • Source of anxiety, avoidance, and loss (Vincent, 2019) Reliance on external sources…”
Section: Categories Contributors Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Autistic students, however, encounter unique experiences in this pursuit as they participate as a minority group on campus with the majority of their peers and instructors being nonautistic (Gerstle & Walsh, 2011;Lucas et al, 2021;Prince, 2013). Some nonautistic instructors report experiencing challenges in working with the growing number of autistic students on university campuses (Alcorn-MacKay, 2010; Gelbar et al, 2014;White et al, 2016) and offer a variety of personal accounts of strategies which the instructors believe to have been helpful (Brown et al, 2014;Gerstle & Walsh, 2011;Jurecic, 2006Jurecic, , 2007Roberts & Birmingham, 2017).…”
Section: Academic Writing and The Social Turnmentioning
confidence: 99%